OBESITY BECOMES A GLOBAL PROBLEM: Received: 05th October 2023; Revised: 20th December 2023, 12th January 2024; Accepted: 20th January 2024 - Lubis, Fitri Halimah; Erpiani; Lailan; Ananda, Ayu; Ismah, Zata (LIFE: International Journal of Health and Life-Sciences, 2024)
Obesity is a common disease that can cause and increase cardiovascular disease, diabetes, cancer, and more. This may indicate that obesity may affect genome stability. Obesity is a global problem, especially in high-income countries. The aim of this research is to identify diseases and cases associated with obesity. Methodology: The method used is a case study where the author analyzes an existing problem and arranges it systematically. Conclusion: Obesity is a disease that has a risk of causing the development of other diseases. Obesity has a major impact on physical and mental health. The factors that can cause obesity are genetics, environment, socio-economics and drugs.